MEMBANGUN KESADARAN MASYARAKAT MENGENAL KESEHATAN LINGKUNGAN MELALUI PEMANFAATAN LIMBAH PLASTIK MENJADI ECOBRICK DI DESA GUNUNG MALANG KECAMATAN PRINGGABAYA KABUPATEN LOMBOK TIMUR - Alfiqri, Rizal Fahmi; Anugrah, Muhammad Ihsan; Fachri, Zul; Akbar, Jaelani Muhammad; Olivianti, Anisa; Ramdani, Nursuci; Hadiyawati, Titin; Fitria, Fitria; Oktaviana, Nuriastika; Zannah, Raodatul (Universitas Mataram, 2023)
The Real-Thematic Work Lecture activity was carried out in Gunung Malang Village, Pringgabaya District, East Lombok Regency which aims to introduce the public to environmental health through managing plastic waste to become ecobricks. This activity is carried out using the descriptive method, this method is more suitable for use because it describes problems that occur in the present or are ongoing. To introduce the community about ecobricks, socialization and training is carried out in each hamlet. Apart from wanting to be more involved with the community, it is hoped that any knowledge that is shared can be conveyed properly.